Downconversion and upconversion observed from Er3+/Yb3+/Eu3+ tri-doped-Y2O3 for application in energy conversion - Mayrinck, Caroline de; Siqueira, Renato L.; Esbenshade, Jennifer; Schiavon, Marco Antônio; de Lima, Renata C.; Barbosa, Helliomar P.; Lima Ribeiro, Sidney José [UNESP]; Ferrari, Jefferson Luis (Elsevier, 2020)
Inorganic oxides doped with RE3+ have interesting optical properties for converting photons into higher and/or lower energy from excitation, ultraviolet (UV) or infrared (IR). The luminescence materials Y2O3:Yb3+,Eu3+,Er3+ (xYb: 1.2; xEu: 2.0; xEr: 0.1–3.0 mol%) were successfully prepared using different precursors, NH4OH (ammonium hydroxide), H2C2O4 (oxalic acid), C6H8O7 (acid citrate) and CH4N2O (urea). The as prepared materials were annealed at 900, 1000 and 1100 °C. The crystalline structure and morphology of these materials were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), UV excited and upconversion photoluminescence. Structural investigation of materials exhibited formation of the cubic phase, indicating efficient doping ions in the matrix. In the analysis of the diffractograms, the use of the Scherrer equation showed the increase of the crystallite size by increasing the annealing temperature. There was also a small variation in the microstrain values of materials indicating the possible presence of structural defects. Photoluminescence investigations indicate that all the precursors used are favorable for the synthesis verified from the intense luminescence of the materials. Y2O3:Yb3+,Eu3+,Er3+ to be excited simultaneously at 394 and 980 nm, which exhibited emission narrow bands at 524 nm, 541 nm, 662 nm and 601 nm, 612 nm, assigned to the Er3+ and Eu3+ ion, respectively. There is a cross relaxation process due to decreased lifetime values (between 0.73 and 1.69 ms) when compared to materials doped with Eu3+ alone. In all materials, the amount of dopant was observed to not influence the morphology of the materials or the photoluminescent properties, providing potential applications in energy conversion, specific in solar cell.
Keywords: Energy conversion; Rare earths; Solar cells; Upconversion